In Brief: Myeloid‐derived suppressor cells in cancer. Issue 1 (21st March 2017) - Solito, S; Pinton, L; Mandruzzato, S
Abstract: The role of myeloid‐derived suppressor cells (MDSCs) in cancer development has become clear over recent years, and MDSC targeting is an emerging opportunity for enhancing the effectiveness of current anticancer therapies. As MDSCs are not only able to limit anti‐tumour T‐cell responses, but also to promote tumour angiogenesis and invasion, their monitoring has prognostic and predictive value. Herein, we review the key features of MDSCs in cancer promotion. © 2017 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.